GEOGRAPHIC INFORMATION SYSTEM-BASED EVALUATION OF THE ECOLOGICAL CONNECTIVITY INDEX MAP ACROSS PATCH SIZE SPECTRUMS: A CASE STUDY OF MAKASSAR CITY - Ibrahim Djamaluddin; Poppy Indrayani; Ritnawati Makbul; Yasuhiro Mitani; Panji Nilo Suwarno (Universitas Trisakti, 2025)
Aims: This paper investigates the ecological functional areas of Makassar City by utilizing land cover spatial data from 1997 and 2012 to evaluate ecological connectivity through Geographic Information Systems (GIS). Methodology and results: A spatial analysis of these ecological functional areas was conducted across different patch size categories to assess the percentage distribution of each land-use type. Additionally, the comparative distribution of the Ecological Connectivity Index (ECI) map for Makassar City was simulated. The findings indicate a decline in connectivity levels in previously natural areas surrounding Makassar, particularly in the western and eastern regions of the city. The ECIs have significantly decreased from 1997 to 2012, primarily due to the impacts of urban development in low-density, dispersed suburban areas. The results suggest that optimal quantitative criteria for ecological functional areas at the city scale of Makassar can be classified within patch size spectrum III. Implementing well-designed strategies could help mitigate the loss of ecological connectivity, thereby supporting the protection and restoration of Makassar’s environmental integrity. Conclusion, Significance, and Impact of Study: from a landscape ecological perspective, a significant trend observed in Makassar City over the past fifteen years has been the rapid fragmentation and transformation of its natural landscape. This has led to the emergence of numerous habitat patches that are progressively smaller and more disconnected. A thorough understanding of the interactions between spatial patterns and ecological processes across various scales is essential for effective landscape and environmental studies.